2016
DOI: 10.1021/acs.jmedchem.6b00653
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Dissociation of Ligands from the Adenosine A2A Receptor through Modulation of Salt Bridge Strength

Abstract: The association and dissociation kinetics of ligands binding to proteins vary considerably, but the mechanisms behind this variability are poorly understood, limiting their utilization for drug discovery. This is particularly so for G protein-coupled receptors (GPCRs) where high resolution structural information is only beginning to emerge. Engineering the human A2A adenosine receptor has allowed structures to be solved in complex with the reference compound ZM241385 and four related ligands at high resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
200
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(234 citation statements)
references
References 43 publications
(89 reference statements)
13
200
0
6
Order By: Relevance
“…The rational ligand design came from the reported crystal structures of the hA 2A AR bound to ZM241385, providing a clear blueprint of ligand binding interactions [13, 14, 31]. A deep, planar, and narrow cavity holds the aromatic core and furan ring of ZM241385, while the phenylethylamine substituent is directed to the extracellular region (EL2 and EL3).…”
Section: Discussionmentioning
confidence: 99%
“…The rational ligand design came from the reported crystal structures of the hA 2A AR bound to ZM241385, providing a clear blueprint of ligand binding interactions [13, 14, 31]. A deep, planar, and narrow cavity holds the aromatic core and furan ring of ZM241385, while the phenylethylamine substituent is directed to the extracellular region (EL2 and EL3).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the A 2A AR consists of seven transmembrane helices (TM1‐TM7) connected by three intracellular loops (ICL1–ICL3) and three extracellular loops (ECL1–ECL3) . The receptor has been crystallized in complex with agonists, including adenosine, antagonists, and coupled to a G protein fragment . The A 2A AR has also been crystallized with interacting lipids and sodium ions …”
Section: Introductionmentioning
confidence: 99%
“…The receptor has been crystallized in complex with agonists, including adenosine, antagonists, and coupled to a G protein fragment . The A 2A AR has also been crystallized with interacting lipids and sodium ions …”
Section: Introductionmentioning
confidence: 99%
“…The carboxylic acid of E172 also forms a strong electrostatic interaction with the amino group of the [ 3 H]CCPA ligand. For A 2A R, it has been shown that disruption of the analogous extracellular salt bridge above the orthosteric binding pocket accelerates the dissociation of ligands from A 2A R, while stabilization slows it . In A 2A R, this salt bridge is part of a “triad” of hydrogen bonding interactions that acts as a “cap” over the orthosteric site, preventing influx of water into the receptor that accelerates dissociation .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a common mechanism to both the adenosine and muscarinic receptors is through PAM binding with direct molecular interaction with specific residue side chains that are involved in necessary side‐chain rearrangements required for agonist ligand dissociation. Namely, (1) the adenosine receptors (A 1 R, A 2A R) PAMs were predicted to interact directly with the specific salt bridge residue pairs that have been implicated in ligand dissociation kinetics, and (2) muscarinic receptors PAMs may form direct molecular interaction with analogous salt bridge residues, such as 12 shown in Figure a, where the carboxylic acid group interacts with lysine K392, forming a salt‐bridge electrostatic interaction with residue Y179 (ECL2). Induced fit docking results also show that compounds 13 , 14 , and 19 may also bind and induce new analogous side chain interactions mediated by Q177 (ECL2) that would stabilize the receptor.…”
Section: Discussionmentioning
confidence: 99%